Film work of the Samara Provincial Community of Consumer Cooperatives in 1926–1928 - E. V. Dianova (Вестник Самарского университета: История, педагогика, филология, 2023)
The article deals with the film work of the Samara Provincial Community of Consumer Cooperatives in 1926–1928. The relevance of the research topic lies in the fact that, using the example of the activities of the regional cooperative union for film services to the population, it is possible to identify social factors and mechanisms of sociocultural dynamics. As a source, the materials of the magazines «Sower of Truth» of the Samara Provincial Community of Consumer Cooperatives and «Cooperative Way» of the Middle Volga Regional and District Union of Consumer Cooperatives were used. The magazines published announcements of films, announcements about the route of film shifts, instructors’ reports on film flights, and reviews from viewers. The main scientific problem is to study the ways of organizing cinema services and the results of the work of cooperative movements of the Samara Provincial Union of Consumer Cooperatives. The research methodology is based on the theory of communication. For an objective quantitative analysis of the content of communication, content analysis is used. Narrative, historical-genetic, historical-comparative, typological methods of scientific knowledge were also used. In the course of the study, it was possible to find out that the Samara cooperators used a competent strategy to attract viewers, relying on active shareholders who fully paid their share contributions, subscribers of the Sower of Truth magazine. During film screenings, before and after the films were shown, new members of the cooperatives and subscribers of the Sower of Truth magazine were recruited, and share contributions were accepted. This policy of the Gubernia Union provided a return on the rental of tapes and film flights. The organization of movie nights was linked to various socio-political and cooperative educational campaigns.